Perancangan Kriptografi Blok Cipher Berbasis Pola Gambar Rumah Adat Joglo - Bramantya, Samuel Dwi; Pakereng, Magdalena A. Ineke (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Cryptography is a scientific discipline used to maintain data security. To increase the level of security, cryptographic development is needed by implementing 64 bit Block Cipher Cryptography based on the Joglo traditional house image pattern. This approach produces random ciphertext, which is useful in changing data in the form of clear messages (plaintext) into messages that cannot be understood (ciphertext). The designed pattern is 64 bits long and then converted back into plaintext. This cryptographic design is based on the description of the Joglo traditional house, using encryption and decryption processes combined with XOR operations. The S-Box substitution table is used for byte transposition, which aims to obtain Ciphertext. The research results show that the 64 bit block cipher cryptographic system by applying the avalanche effect to the Joglo traditional house image pattern can be considered an effective cryptographic system. The correlation value achieved reached 53.125%, validating its ability to maintain data security.
Keywords: Block Cipher; Cryptography; Joglo Traditional House; S-Box